Bio-assay- guided fractionation and chromatographic profiling of the hexane extract from the leaves of "tanga-tanga", Prunus Grisea. - Torres, Charmaine G. (Asia-Pacific Journal of Science, Mathematics, and Engineering, 2014)
Prunus Grisea, locally known as "tanga-tanga", belongs to the Rosacae family and Genus Prunus. This study is focused on the bioassay-guided partial isolation of the bioactive fractions from the hexane extract of the air-dried leaves of Prunus grisea, denoted as PGH, employing various chromatographic methods. Gravity column chromatography of PGH afforded the 14 fractions PGH1-PGH14. Fraction PGH13 exhibited the highest bioactivity against the brine shrimp Artemia salina Leach with mortality of 56.67%. Subsequent purification of fraction PGH13 gave the six sub-fractions PGH13.1-PGH13.6 which were subjected to high-performance liquid chromatographic profiling and analysis. These possibly purified sub-fractions were identified and recommended for structure elucidation and further bioactivity tests.